Knowledge Solutions: Tools, Methods, and Approaches to Drive Organizational Performance - Serrat, Olivier (Cham Springer Nature, 2017)
strategy development; collaboration; knowledge sharing; knowledge capture; storage
English
Keywords: Library & information sciences; strategy development; collaboration; knowledge sharing; knowledge capture; storage